The effect of noise barriers on viaducts on pollutant dispersion in complex street canyons - Tingzhen Ming; Fangyan He; Yongjia Wu; Tianhao Shi; Changrong Su; Caixia Wang; Zhengtong Li; Wei Chen; Renaud de Richter (Energy and Built Environment, 2023)
The noise reduction effect of noise barriers has been extensively studied, but the effect on pollutant dispersion remains unclear. A computational fluid dynamics (CFD) simulation is conducted to investigate the effects of different heights, lengths, and types of noise barriers and different wind speeds on pollutant dispersion in street canyons with viaducts. The field synergy theory of the convective mass transfer process is used for quantitative analysis of pollutant dispersion in street canyons. The results show that as the height and length of the noise barrier increase, the pollutant dispersion capacity decreases. As the wind speed increases, the rate of decrease in the average CO concentration declines. The effect of the wind speed on the synergistic improvement of the speed and concentration gradient vectors differs for different types of noise barriers. The performance follows the order: fully-closed noise barrier > left noise barrier > right noise barrier > semi-closed noise barrier. The different noise barrier types significantly impact the flow field and pollutant dispersion and reduce the CO concentration to varying degrees, except for the fully-closed type. The average CO concentration in the pedestrian breathing zone is reduced by a maximum of 55.85% on the leeward side and by 53% on the windward side, indicating that an appropriate noise barrier on the viaduct reduces noise pollution and improves the air quality in street canyons, especially in the pedestrian breathing zone.